Prescription pattern study of antiasthmatics drugs in tertiary care centre - Gawali, Ujwala P.; Gholve, Parmeshwar B.; Rizvi, Salman H.; Mishra, Prashant S. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Bronchial asthma is a social and economic healthcare burden. Drug Utilization studies can play a key role in helping the healthcare system to understand, interpret and improve the prescribing administration & use of medications. Methods: A prospective, Cross-sectional, Observational study was conducted at inpatient and outpatient Department of Medicine and Paediatrics in tertiary health care centre. As per inclusion criteria, 127 patients with asthma were interviewed, and prescription data was recorded in a pre-designed case record form from 1 October 2018 to 31 December 2018. Results: A total of 127 prescriptions were studied. It was observed that majority of the study patients were in the age group of 40-50 years, with 83 (65.5%) males and 44 (34.6%) females. Most of the patients were of Mild intermittent asthma 65 (51.18 %) followed by patients with Mild persistent asthma 31 (24.40 %). 10 different anti-asthmatics drugs were prescribed along with adjunctive medicines. Most of the patients received multiple drug therapy 98 (77.16 %). Prevalence of two drug combination was the highest 74 (58.26 %) followed by monotherapy29 (22.83 %). Most common route of drug administration was inhalational route followed by oral route. β2 agonists and corticosteroids were the most commonly prescribed combination drugs followed by methylxanthines. 103 (81.10 %) prescription contains both generic and brand drugs compared to generic names only 16 (12.59 %) and brand names only 8 (6.29 %). Conclusions: This study concluded that the present prescribing practice in asthma therapy in tertiary care centre is not sufficiently rational. Hence, it is necessary to encourage physicians to follow asthma guidelines while managing asthmatic patients.